2021
DOI: 10.1002/ctm2.377
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of CLTC interacts with TFG, facilitating osteosarcoma via the TGF‐beta and AKT/mTOR signaling pathways

Abstract: 1. High CLTC expression is associated with worse clinical outcomes in osteosarcoma patients. 2. Inhibition of CLTC suppresses osteosarcoma growth both in vitro and in vivo.3. SP1 binds to the CLTC promoter to promote the transcriptional activity of CLTC in osteosarcoma. 4. CLTC-mediated oncogenic effects occurred through activation of the TGF-beta and AKT/mTOR signaling pathway in a TFG-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This abnormal fusion gene is also thought to be a major factor in congenital primitive plasmacytoid dendritic cell tumors ( 59 ). The high expression of CLTC has also been shown to be an independent prognostic factor for tumor-free survival and overall survival in patients with osteosarcoma ( 60 ). Transcriptome analysis revealed that CLTC–TFE3 fusion is present in renal cancer and affects many downstream cancer-related pathways ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…This abnormal fusion gene is also thought to be a major factor in congenital primitive plasmacytoid dendritic cell tumors ( 59 ). The high expression of CLTC has also been shown to be an independent prognostic factor for tumor-free survival and overall survival in patients with osteosarcoma ( 60 ). Transcriptome analysis revealed that CLTC–TFE3 fusion is present in renal cancer and affects many downstream cancer-related pathways ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, clathrin-heavy chain 1 (CLTC1) is an essential substance for the formation of membrane-invaginated vesicles and is involved in clathrin-independent endocytosis (CIE) and mitosis (Bond et al, 2018, Doherty andMcMahon, 2009). CLTC is associated with tumorigenesis, and Cheng Dongdong et al found that it is an important prognostic factor for OS patients and promotes tumor cell proliferation (Shijie et al, 2021). However, the molecular mechanism underlying OS needs further investigation.…”
Section: Umi-77 and Curcumin Synergistic Treating Osteosarcoma In Viv...mentioning
confidence: 99%
“…In addition, NF-κB could combine with the regulatory sequence of the vimentin gene promoter to promote Twist expression and induce the EMT process [19,20]. The AKT/mTOR signaling pathway is frequently dysregulated in malignancies and plays a key role in numerous biological processes, including growth, proliferation, and survival [21,22]. Current research indicates that the AKT/mTOR pathway is critical for the malignant tumor EMT process [23,24].…”
Section: Introductionmentioning
confidence: 99%